Investigating disease risk associated with feed delivery - Bottoms, K.; Dewey, Catherine E.; Poljak, Z.; Carter, N.; Richardson, K. (2013)
BACKGROUND – Certain pathogens can be spread between farms via fomites, including contaminated boots, clothing, hands, and vehicles. Additionally, feed and/or specific protocols for the delivery of feed have been associated with the transmission of swine diseases. This project allowed for the identification of economically and logically feasible management changes at the feed company and farm level that will reduce the potential for disease transmission associated with the delivery of feed. METHODOLOGY – Initially, discussions with swine producers and feed company personnel (managers, dispatchers, truck drivers) explored what current protocols are used in the industry to address the potential for disease spread via feed delivery, and to identify possible changes that could further reduce that risk. Next, a 6-week pilot study was conducted in order to collect information about what is currently happening in the industry, to determine the frequency of some of the identified issues in the day-to-day delivery of feed, and to trial the use of reusable rubber boots. RESULTS – The pilot study included 3 feed companies, 40 feed truck drivers, and 2202 farm visits. Some key results are summarized below: More than half of the deliveries were to pig farms (59%). The rest were to poultry (26%), ruminant (14%), or farms with multiple types of animals (1%). •The majority of deliveries were for bulk feed only (84%); the remaining deliveries were for bags only (6%), or for bulk and bagged feed (10%) •The truck driver didn’t enter the barn 93% of farm visits. The rest of the time, the driver entered the office (1%), the barn (5%), or an area with animals (2%) • The farm lane was clean on 82% of farm visits. In some cases, though, the driver noticed mud and/or puddles (20%), manure (2%), or dead animals (1%) • Dead stock management was adequate on 91% of farm visits, however the driver noted dead stock where he/she had to drive or walk on 3% of visits •The feed bin area was clean 81% of the time, but there was spilled feed on 16% of farm visits • Reusable rubber boots were worn on 21% of farm visits; the rest of the time drivers wore disposable (7%) or their own personal boots (72%). • The boots cost between $6.50 and $16 per pair, and the cost of cleaning boots was $1.75 per pair BENEFITS TO THE SWINE INDUSTRY – This project has encouraged feed company personnel and swine producers to think about the issue of biosecurity in the feed industry. In particular, increasing awareness of biosecurity among the different players, and encouraging producers to be aware of what they can do to protect the industry as a whole. Overall, the participants appreciated our approach, and have expressed keen interest in understanding their place in this issue.